PENDAMPINGAN PENYUSUNAN MODUL AJAR BAHASA INGGRIS SMK BERMUATAN PROJECT BASED LEARNING - Praditya Putri Utami; Evi Karlina Ambarwati; Indah Purnama Dewi; Nina Puspitaloka; Audry Adiananta; Intan Akhna Khatami (Jurnal Abdi Insani, 2023)
The development of technology and education today has grown very rapidly that education needs to instill students' ability to solve problems, one of which is project-based learning (PjBL). However, there are still some difficulties in implementing project-based learning including teachers’ lack of skills and understanding to implement this model. Therefore, this community service program aims to provide knowledge of the principle of project based learning as well as train teachers to design lesson plans which resonates project based learning. The training activities were carried out at SMK Negeri 1 Cikampek on August 14, 2023. The participants of this training were 95 vocational English teachers in Karawang, West Java. In the implementation of training activities, there are several stages that are passed, namely the preparation, implementation and evaluation stages. The implementation of the training activities began with a presentation of material regarding an overview of the implementation of PjBL in the preparation of vocational English teaching modules followed by a demonstration of examples of English projects in various classroom contexts and the practice of preparing teaching modules. The activity went well with two points of achievement, namely understanding or knowledge and products in the form of an effective and efficient teaching module framework. Based on the results of the training that has been carried out, the emphasis in the practice of preparing project-based teaching modules is still not optimal as there are several groups that have not completed the preparation of teaching modules due to limited time constraints.